KAJI EKSPERIMENTAL DAN NUMERIK KINERJA CYCLO DUST FILTER - Prihadi Setyo Darmanto; Joko Sarsetyanto (Mesin, 2004)
One of the methods for increasing separation efficiency of a cyclone is to implement a fabric filter at its inner tube. The combination of cyclone separator and fabric filter in commonly called as cyclo-dust filter. This paper presents an experimental study of the performance test of cyclo-dust filter and CFD numerical simulation of the flow inside this apparatus. The experiment was conducted for some variation of filter area. The results show that the separation efficiency of more than 99% was observed. This value is normally very difficult to reach with a normal cyclone separator. The pressure drop rises with the increasing of fabric's area. However this increase of pressure drop is not proportional to the increase of the fabric's area. The CFD simulation was also used for determining the best position of inlet duct.